2009
DOI: 10.1136/gut.2009.181834
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a regulates intestinal membrane permeability in patients with irritable bowel syndrome

Abstract: Background-The molecular mechanisms underlying the pathophysiology of irritable bowel syndrome (IBS) are poorly understood. One mechanism may involve increased intestinal permeability that is reversed with glutamine supplementation. Our goal was to evaluate the expression of glutamine synthetase and its complementary miRNA in blood microvesicles and gut tissues of IBS patients with increased intestinal membrane permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
210
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(229 citation statements)
references
References 52 publications
15
210
1
3
Order By: Relevance
“…In agreement to our finding, Zhou et al 41 also found miR29 family member 'miR29a' involvement in the regulation of intestinal membrane permeability in patients with irritable bowel disease. 41 Further, we studied cause-effect relation of miR29b induction with the expression levels of junction proteins that maintain BBB integrity along with oxidative stress and other molecular events in vivo (HHcy) mice model. Compared with WT, HHcy mice brain indicated signs of oxidative stress (gain of NOX-4), drop in endothelial function (loss of eNOS), and diminish synaptic plasticity (SAP-97).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement to our finding, Zhou et al 41 also found miR29 family member 'miR29a' involvement in the regulation of intestinal membrane permeability in patients with irritable bowel disease. 41 Further, we studied cause-effect relation of miR29b induction with the expression levels of junction proteins that maintain BBB integrity along with oxidative stress and other molecular events in vivo (HHcy) mice model. Compared with WT, HHcy mice brain indicated signs of oxidative stress (gain of NOX-4), drop in endothelial function (loss of eNOS), and diminish synaptic plasticity (SAP-97).…”
Section: Discussionsupporting
confidence: 93%
“…The effect of MiR-29a on intestinal permeability might be due to the regulation of glutamine synthetase [94]. MiR-29a and MiR-29b also reduced the levels of CLDN1 mRNA and increased intestinal permeability [95].…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
“…[105][106][107] Studies focused on permeability assessment using urinary recovery of orally administered sugars or radioisotopes (Table 3) reported increased permeability in the small intestine, 22,108,109 with the exception of one study performed in children. 60 Several studies also highlighted an increased colonic permeability 60,71,[109][110][111] ; however, this result could not be consistently replicated by other groups. 108,112 Two groups have examined whether the altered intestinal permeability observed in IBS patients could arise from an improper response of the intestinal barrier to noxious agents rather than intrinsic defects.…”
Section: Intestinal Permeability In Ibs Patientsmentioning
confidence: 99%